Evaluating follow-up and complexity in cancer clinical trials (EFACCT): an eDelphi study of research professionals' perspectives. Issue 2 (18th February 2020) - Jones, Helene Markham; Curtis, Ffion; Law, Graham; Bridle, Christopher; Boyle, Dorothy; Ahmed, Tanweer
Abstract : Objectives: To evaluate patient follow-up and complexity in cancer clinical trial delivery, using consensus methods to: (1) identify research professionals' priorities, (2) understand localised challenges, (3) define study complexity and workloads supporting the development of a trial rating and complexity assessment tool (TRACAT). Design: A classic eDelphi completed in three rounds, conducted as the launch study to a multiphase national project (evaluating follow-up and complexity in cancer clinical trials). Setting: Multicentre online survey involving professionals at National Health Service secondary care hospital sites in Scotland and England varied in scale, geographical location and patient populations. Participants: Principal investigators at 13 hospitals across nine clinical research networks recruited 33 participants using pre-defined eligibility criteria to form a multidisciplinary panel. Main outcome measures: Statements achieving a consensus level of 70% on a 7-point Likert-type scale and ranked trial rating indicators (TRIs) developed by research professionals. Results: The panel developed 75 consensus statements illustrating factors contributing to complexity, follow-up intensity and operational performance in trial delivery, and specified 14 ranked TRIs. Seven open questions in the first qualitative round generated 531 individual statements. Iterative survey rounds returned rates of 82%, 82% and 93%. Conclusions: Clinical trials operate within a dynamic, complex healthcare and innovation system where rapid scientific advances present opportunities and challenges for delivery organisations and professionals. Panellists highlighted cultural and organisational factors limiting the profession's potential to support growing trial complexity and patient follow-up. Enhanced communication, interoperability, funding and capacity have emerged as key priorities. Future operational models should test dialectic Singerian-based approaches respecting open dialogue and shared values. Research capacity building should prioritise innovative, collaborative approaches embedding validated review and evaluation models to understand changing operational needs and challenges. TRACAT provides a mechanism for continual knowledge assimilation to improve decision-making.